A lifecycle analysis of complex public procurement: an agency-institutional theory perspective - Forster, Rick; Lyons, Andrew; Caldwell, Nigel; Davies, Jennifer; Sharifi, Hossein (Emerald, 2025)
Purpose The study sets out to demonstrate how a lifecycle perspective on complex, public-sector procurement projects can be used for making qualitative assessments of procurement policy and practice and reveal those procurement capabilities that are most impactful for operating effectively. Design/methodology/approach Agency theory, institutional theory and the lifecycle analysis technique are combined to abductively develop a framework to identify, analyse and compare complex procurement policies and practices in public sector organisations. Defence is the focal case and is compared with cases in the Nuclear, Local Government and Health sectors. Findings The study provides a framework for undertaking a lifecycle analysis to understand the challenges and capabilities of complex, public-sector buyers. Eighteen hierarchically-arranged themes are identified and used in conjunction with agency theory and institutional theory to explain complex procurement policy and practice variation in some of the UK’s highest-profile public buyers. The study findings provide a classification of complex buyers and offer valuable guidance for practitioners and researchers navigating complex procurement contexts. Originality/value The lifecycle approach proposed is a new research tool providing a bespoke application of theory by considering each lifecycle phase as an individual but related element that is governed by unique institutional pressures and principal-agent relationships.
Keywords: Procurement lifecycle analysis; Procuring complex performance; Complex procurement; Agency theory; Institutional theory; 35 Commerce, Management, Tourism and Services; 3507 Strategy, Management and Organisational Behaviour; Generic health relevance; Business & Management; 3507 Strategy, management and organisational behaviour; 3509 Transportation, logistics and supply chains